Names in the Mass Media Texts - Elena V. Glinka (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2019)
The proper name in the texts of the media is one of the ways to express the author’s modality, appraisal and a means of attracting the attention of the reader. Therefore, most often precedent names are found in the most significant and strong positions of the media text: in the headline set or at the end of the article. Precedents include names that are known to all (or many) representatives of the national-cultural community, as well as relevant in terms of current events. The article analyzes the texts of a number of Belarusian printed publications of 2019, where names in headings and leads are not only a means of attracting attention, but also a factor in enhancing the expressiveness of the text and expression of appreciation.